DATA WAREHOUSE KEPEMILIKAN MCK MENGGUNAKAN METODE ETL DAN BLACK-BOX (STUDI KASUS: KELURAHAN NITU, NTB) - I Putu Agus Eka Pratama; Muhammad Syakurrahman (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2023)
Preparation of government policies related to public services and facilities requires population data and its supporting technology. The Government of Bima, West Nusa Tenggara (NTB) has population data related to the ownership of each family in Nitu Village but is constrained by the technology to process these data. This research designs and implements a Data warehouse using the Extraction, Transformation, and Loading (ETL) method with the concept of multi-dimensional data. The system is implemented using Pentaho, then tested using the Black-Box method. The Data warehouse collects data from residents of the Nitu Kelurahan related to MCK ownership, then processed it to produce reports and data visualization. The stages of the research include data collection, identification of data dimensions, design, implementation, and Testing of the Data warehouse, as well as conclusions. The final results of the research show that the Data warehouse that was built helps the government in determining policy strategies and making decisions regarding the provision of MCK facilities for the people of Nitu Village, through reports and data visualization